Preservation of behavioural functions by haruan traditional extract (HTE) in rats with ketamine-induced neurodegeneration - Mohd Shafri, Mohd Affendi; Mohamed, Farahidah; Md. Jaffri, Juliana; AM, Mat Jais (2011)

(untitled)
INTRODUCTION Behavioural dysfunction presents as a significant problem in ketamine-induced brain damage. Restoration of brain functions following neurodegenerative damage may be possible using a neurorestorative agent with good lipophilicity, antioxidative and neuromodulatory properties. One such agent, haruan traditional extract (HTE), has been indicated as a neuroregenerative agent in in vitro study using PC12 cells and here is studied for its neuroprotective property. MATERIALS & METHODS The neuroprotective assay involves HTE (oral, 100ul/100mg body weight, once daily for 6 weeks) being given to Sprague Dawley (male, 7-8 weeks old, 150-200 gram), prior to induction of neurodegeneration by ketamine. Ketamine (i.p., 20mg/kg body weight, 4 times daily at 2 hourly interval) is given as either short exposure (1 day) or long exposure (5 days). Neurobehavioural test using hole board maze (5 minutes, 40cm x 40 cm Plexiglass raised floor, 16 x 3 cm diameter holes) was done to assess functions such as nose dipping and rearing activities. RESULT AND DISCUSSION Restoration of nose dipping and rearing activities show significant differences between short and long ketamine exposure group. CONCLUSION Statistical analyses comparing the groups indicate that HTE may be able to exert neuroprotective effect.